2022
DOI: 10.1080/0886022x.2022.2042310
|View full text |Cite
|
Sign up to set email alerts
|

Patients receiving hemodialysis do not lose SARS-CoV-2 antibodies more rapidly than non-renal controls: a prospective cohort study

Abstract: Background Patients with end-stage kidney disease receiving maintenance hemodialysis (HD) are at increased risk for mortality after infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) compared with the general population. However, it is currently unknown whether the long-term SARS-CoV-2 humoral and cellular immune responses in patients receiving HD are comparable to individuals with normal kidney function. Method The prospective cohort study incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…These findings implied that the COVID-19 vaccines were well tolerated among HD patients although they experienced a variety of adverse reactions. A recent study reported that patients receiving HD maintained some immune responses following natural COVID-19 infection [ 15 ]. Vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…These findings implied that the COVID-19 vaccines were well tolerated among HD patients although they experienced a variety of adverse reactions. A recent study reported that patients receiving HD maintained some immune responses following natural COVID-19 infection [ 15 ]. Vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…It has not been clarified yet with certainty as to whether hemodialysis patients can further extend their immune response after a fourth vaccination. Interestingly, even if the immune response of a COVID-19 vaccination is less pronounced in hemodialysis patients compared to the normal population, there are indications that immune responses might be sustained in those hemodialysis patients who develop antibody responses 11 .…”
Section: Introductionmentioning
confidence: 99%